[PP.38.02] THE AMBULATORY HYPOTENSIVE EFFECT OF AEROBIC TRAINING: A REAPPRAISAL THROUGH A META-ANALYSIS OF SELECTED MODERATORS. (September 2016) - Sosner, P.; Guiraud, T.; Gremeaux, V.; Arvisais, D.; Herpin, D.; Bosquet, L.
Abstract : Objective: The effectiveness of regular exercise in decreasing both systolic and diastolic blood pressure (BP) is well-established. Our purpose was to assess the impact of both subject and physical activity program characteristics on ambulatory BP through a meta-analysis of the existing literature. Design and method: Three databases (PubMed, Embase, Web-of-Science) were searched using relevant terms and strategies. From 637 identified records, 37 studies met inclusion criteria: details about training intervention and participant characteristics, pre- and post-training ambulatory BP measurements, at home (HBPM) or during 24-h (ABPM). Results: The weighted mean difference was for 24-h systolic/diastolic ABPM (n = 847 participants): -4.06/-2.77 mmHg (95%CI: -5.19 to -2.93 / -3.58 to -1.97; P < 0.001), for daytime (ABPM or HBPM, n = 983): -3.78/-2.73 mmHg (95%CI: -5.09 to -2.47 / -3.57 to -1.89; P < 0.001) and nighttime ABPM periods (n = 796): -2.35/-1.70 mmHg (95%CI: -3.26 to -1.44 / -2.45 to -0.95; P < 0.001). Characteristics significantly influencing BP improvement were: an initial office BP > = 130/85 mmHg and diet-induced weight-loss. We found no differences in standardized mean difference (SMD) according to sex, age, or training characteristics (intensity, number of sessions, training duration) (Fig. 1). Figure. No caption available. Conclusions: Antihypertensive effects of aerobic training assessed by ambulatory BP measurements appear significant and clinically relevant for both daytime and nighttime periods, in particular for participants with an office BP > = 130/85 mmHg.